The role of foreign intermediary relationship quality on export performance: A survey on Turkish firms - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
Foreign intermediary relationship has been one of the most important topics in the analysis of export performance. This study evaluates the effects of foreign intermediary relationship quality on export performance. Relying on literature related to the subject, effects of cooperation, trust and commitment on export performance have been analysed. Using survey data from 104 managers working in export organizations located in Istanbul, a conceptual model is tested in which cooperation, trust and commitment act as dimensions of intermediary relationship quality construct. By studying data obtained and using regression analysis, we found that commitment was postively related with export performance. This study contributes to understanding the role of intermediary relationship on export performance.
Keywords: foreign intermediary; export performance; relationship quality; trust quality; cooperation; EMPIRICAL LINK; COMMITMENT; DETERMINANTS; VENTURES; TRUST; INTERNATIONALIZATION; ANTECEDENTS; ADAPTATION; BEHAVIOR; IMPACT